2016
DOI: 10.18632/oncotarget.12237
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of tumor growth by circulating full-length chromogranin A

Abstract: Chromogranin A (CgA), a neuroendocrine secretory protein, and its fragments are present in variable amounts in the blood of normal subjects and cancer patients. We investigated whether circulating CgA has a regulatory function in tumor biology and progression. Systemic administration of full-length CgA, but not of fragments lacking the C-terminal region, could reduce tumor growth in murine models of fibrosarcoma, mammary adenocarcinoma, Lewis lung carcinoma, and primary and metastatic melanoma, with U-shaped d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 43 publications
(46 reference statements)
0
32
0
Order By: Relevance
“…Of note, CgA alone could also delay tumor growth in some models. This was not unexpected because we have previously shown that CgA can inhibit tumor growth by inhibiting angiogenesis (31).…”
Section: Cga Does Not Prevent the Antitumor Activity Of Doxo In Murinmentioning
confidence: 65%
See 2 more Smart Citations
“…Of note, CgA alone could also delay tumor growth in some models. This was not unexpected because we have previously shown that CgA can inhibit tumor growth by inhibiting angiogenesis (31).…”
Section: Cga Does Not Prevent the Antitumor Activity Of Doxo In Murinmentioning
confidence: 65%
“…An important point that deserves to be discussed is that the protective activity was obtained with a dose of exogenous CgA that generates 2-4 nM peak plasma levels [i.e., within the 2-5 nM range of physiologic levels of CgA observed in untreated rats (31)]. These findings suggest that endogenous CgA at concentrations close to normal physiologic values have a significant role in cardioprotection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrast-enhanced ultrasound (CEUS) analysis was performed using a high-performance ultrasonographic scanner designed for small-animal imaging (Vevo 2100; Visual Sonics) as described previously (11,26).…”
Section: Contrast-enhanced Ultrasound Analysis Of Tumorsmentioning
confidence: 99%
“…Abnormal levels of immunoreactive CgA have been detected in the blood of patients with neuroendocrine tumors and in several other pathologic conditions, including nonneuroendocrine tumors and cardiovascular, gastrointestinal, renal, and inflammatory disorders (8)(9)(10). Recent studies have shown that full-length CgA (CgA 1-439 ) can regulate the endothelial barrier function, exert antiangiogenic effects at physiologic concentrations, and inhibit tumor growth in various animal models (11)(12)(13). A functional antiangiogenic site is located in the C-terminal region 410-439 and a latent (or less active) site is present in the N-terminal region 1-76, this site requiring proteolytic cleavage for full activation (12).…”
Section: Introductionmentioning
confidence: 99%